Oxidation of Some a-Hydroxy Acids by Pyridinium Fluorochromate in Aqueous Acetic Acid Media-A Kinetic and Mechanistic Study - Zaheer Ahmed, S.; Syed shafi, S.; Sheik Mansoor, S. (Asian Journal of Chemistry, 2012)
Kinetics and mechanism of oxidation of some a-hydroxy acids i.e., glycolic acid, lactic acid or mandelic acid by pyridinium fluorochromate have been studied in aqueous acetic acid medium. The main product of oxidation is oxo acids. The reaction is first order with respect to pyridinium fluorochromate, hydroxy acids and [H+]. The reaction is acid catalyzed. The oxidation of a-deuterio mandelic acid exhibits a substantial primary kinetic isotope effect (kH/kD = 5.58 at 303 K). The reaction has been studied in different percentage of acetic acid-water mixture. A suitable mechanism has been proposed